Pregnancy at 65, risks and complications - Shailja Verma; Krishna Agarwal; Gauri Gandhi (Wolters Kluwer Medknow Publications, 2016)
A 65-year-old postmenopausal pregnant woman was referred with antepartum hemorrhage at 29 weeks of gestation. Postadmission diagnosed with chronic hypertension, gestational diabetes mellitus, valvular heart disease, and placenta previa. Her pregnancy was terminated by cesarean delivery at 32 weeks as she had a bout of bleeding per vaginum. Most of the placenta was adherent with no plane of cleavage; therefore, cesarean hysterectomy was performed. Baby birth weight was 1650 g and was shifted to nursery for observation and mother needed Intensive Care Unit care postcesarean. On the 15th day, both healthy mother and baby were discharged. Although pregnancy is possible in postmenopausal women with hormone support but the incidence of complications remain very high. It raises a need for developing well-laid guidelines for performing in vitro fertilization in older age group women.